Breastfeeding duration and asthma in Puerto Rican children. Issue 6 (6th August 2014) - Rosas‐Salazar, Christian; Forno, Erick; Brehm, John M.; Han, Yueh‐Ying; Acosta‐Pérez, Edna; Cloutier, Michelle M.; Wakefield, Dorothy B.; Alvarez, María; Colón‐Semidey, Angel; Canino, Glorisa; Celedón, Juan C.
Summary Rationale Little is known about breastfeeding and asthma in Puerto Ricans, the ethnic group most affected by this disease in the US. We examined the relation between the currently recommended duration of breastfeeding and asthma in school‐aged Puerto Rican children. Methods Case‐control study of 1, 127 Puerto Rican children aged 6–14 years living in Hartford, Connecticut (n = 449) and San Juan, Puerto Rico (n = 678). Parental recall of breastfeeding was categorized based on duration and according to current guidelines (i.e., none, 0–6 months, and >6 months). Asthma was defined as parental report of physician‐diagnosed asthma and wheeze in the previous year. We used logistic regression for the multivariate analysis, which was conducted separately for each study site and for the combined cohort. All multivariate models were adjusted for age, gender, household income, atopy, maternal asthma, body mass index, early‐life exposure to environmental tobacco smoke, and (for the combined cohort) study site. Results After adjustment for covariates, children who were breastfed for up to 6 months had 30% lower odds of asthma (95% CI = 0.5–1.0, P = 0.04) than those who were not breastfed. In this analysis, breastfeeding for longer than 6 months was not significantly associated with asthma (OR = 1.5, 95% CI = 1.0–2.4, P = 0.06). Conclusions Our results suggest that breastfeeding for up to 6 months (as assessed by parental recall) is associated with decreased odds of asthma in Puerto Rican children, and that there is no additional beneficial effect of breastfeeding for over 6 months. These results support current recommendations on the duration of breastfeeding in an ethnic group at risk for asthma. Pediatr Pulmonol. 2015; 50:527–534. © 2014 Wiley Periodicals, Inc.